2020
DOI: 10.3389/fmicb.2020.531404
|View full text |Cite
|
Sign up to set email alerts
|

Cross Inoculation of Rumen Fluid to Improve Dry Matter Disappearance and Its Effect on Bacterial Composition Using an in vitro Batch Culture Model

Abstract: Environmental pressures of ruminant production could be reduced by improving digestive efficiency. Previous in vivo attempts to manipulate the rumen microbial community have largely been unsuccessful probably due to the influencing effect of the host. Using an in vitro consecutive batch culture technique, the aim of this study was to determine whether manipulation was possible once the bacterial community was uncoupled from the host. Two cross inoculation experiments were performed. Rumen fluid was collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
1
2
Order By: Relevance
“…An effect of the consecutive inoculation was observed for the control tubes and those supplemented with NPA, where DMD decreases from batch A to C, following the same pattern as TG, showing the lowest digestibility for all tubes during the B series. These results differ from those of McDermott et al (2020), who indicated that digestibility of dry matter on ruminal cultures tends to increase with consecutive culturing, due to a microbial adaptation under in vitro conditions, associated with reduced diversity of the microbiome. Nevertheless, Lin et al (2019) demonstrated that adaptation to in vitro conditions may take a long time, and that the transfer-to-transfer process has an impact on fermentative parameters, including gas produced, pH, and short-chain fatty acids produced, which may cause variability in dry matter degradability of our experiment.…”
Section: Dry Matter Disappearancecontrasting
confidence: 99%
“…An effect of the consecutive inoculation was observed for the control tubes and those supplemented with NPA, where DMD decreases from batch A to C, following the same pattern as TG, showing the lowest digestibility for all tubes during the B series. These results differ from those of McDermott et al (2020), who indicated that digestibility of dry matter on ruminal cultures tends to increase with consecutive culturing, due to a microbial adaptation under in vitro conditions, associated with reduced diversity of the microbiome. Nevertheless, Lin et al (2019) demonstrated that adaptation to in vitro conditions may take a long time, and that the transfer-to-transfer process has an impact on fermentative parameters, including gas produced, pH, and short-chain fatty acids produced, which may cause variability in dry matter degradability of our experiment.…”
Section: Dry Matter Disappearancecontrasting
confidence: 99%
“…On the other side, an effect of the consecutive inoculation was observed for the control tubes and those supplemented with NPA, where DMD decreases from series A to C, following the same tendency that TG, showing the lowest digestibility for all tubes during the B series. These results differ from others (McDermott et al, 2020), who indicate that the digestibility of dry matter on ruminal cultures tends to increase with consecutive culturing, due to a microbial adaptation under in vitro conditions, associated with reduced diversity of the microbial ecosystem. Nevertheless, Lin et al, (2019) demonstrate that the adaptation to in vitro conditions may take a long time, and the transfer-to-transfer process has an impact on fermentative parameters, including gas produced, pH, and short chain fatty acids SCFA produced, which may cause variability in dry matter degradability of our experiment.…”
Section: Dry Matter Digestibilitycontrasting
confidence: 99%
“…Fresh rumen fluid is commonly employed as INO for in vitro fermentation. Increasing evidences show that frozen rumen fluid can be also used as INO. Frozen rumen fluid as INO can easily preserve rumen microorganisms, and allows multiple experiments to be carried out on the same fluids to reduce interexperimental variation (8,9). Although strong correlations of DM degradation have been observed between fresh and frozen INO (10), evidence also indicates that frozen INO can alter the fermentation pattern with decreased VFA production and shift of fermentation to favor propionate production (11).…”
Section: Introductionmentioning
confidence: 99%